Oral Lesions as the First Clinical Sign of Multifocal Paracoccidioidomycosis: A Case Report - Pina, Paulo Sérgio; Garcia Júnior, Antônio Roberto; Souza da Silva, Rafael Antônio; da Cunha, Wallena Albuquerque; Pinto Júnior, Décio Santos; Lemos Júnior, Celso Augusto; Esteves, Camilla Vieira (Brazilian Journal of Case Reports, 2025)
To report a multifocal case of paracoccidioidomycosis (PCM) with oral, pulmonary, and adrenal involvement, highlighting diagnostic challenges and the role of dental professionals in early detection. A 50-year-old Brazilian man, smoker, and alcohol user presented with oral ulcers, weight loss, and respiratory symptoms. Clinical, histopathological, and imaging analyses confirmed PCM by Paracoccidioides brasiliensis with pulmonary and adrenal dissemination. Treatment included liposomal amphotericin B, hydrocortisone replacement, and photodynamic therapy (PDT) for oral lesions, followed by sulfamethoxazole-trimethoprim maintenance. Combined therapy led to resolution of oral and cutaneous lesions, respiratory improvement, and adrenal stabilization. After 10 months, the patient showed weight gain and no recurrence. Despite Brazil’s high PCM prevalence, delayed diagnosis remains common due to non-mandatory reporting and limited professional awareness. Oral manifestations preceded systemic symptoms, emphasizing the dentist’s role in early diagnosis. PCM is an underdiagnosed systemic mycosis with potentially severe outcomes. Recognition of oral lesions as early indicators enables timely intervention and prevents systemic complications. Strengthening awareness among dental and medical professionals, along with improved epidemiological surveillance, is essential to enhance prognosis and reduce morbidity.